The Role of General and Study-Related Intraindividual Factors on Academic Learning Outcomes under COVID-19: A Cross-Sectional and Longitudinal Analysis - Nicole Casali; Marta Ghisi; Chiara Meneghetti (MDPI AG, 2022)
Little is known about the intraindividual dispositional factors related to cognitive, behavioral, and emotional academic learning outcomes under COVID-19. This study investigated (i) the associations of intraindividual factors, some related to studying (motivation to learn, self-regulated learning, and study resilience), others more general (soft skills, intolerance of uncertainty) with three situational academic learning outcomes (general distress, online self-regulated learning, study-related emotions), and (ii) the effect of time, intraindividual factors, online self-regulated learning, and study-related emotions on distress and achievement over the following three exam sessions. A total of 331 university students took part in the study during the first Italian nationwide lockdown (T1; March-May 2020). Of those, 121 also completed at least one follow-up (T2: August 2020; T3: September 2020; T4: February 2021). At T1, study-related dispositions and soft skills were positively associated with online self-regulated learning and study-related emotions, while study-related dispositions were also negatively associated with general distress. Intolerance of uncertainty was associated positively with general distress and negatively with study-related emotions. Longitudinal effects of T2 and T3 for intolerance of uncertainty and study-related emotions were observed for distress, while those for T4 were study-related dispositions for achievement. Nurturing intraindividual factors can help students cope with a prolonged stressful situation such as a pandemic.